The Effect of Cooperative Learning Model Type Think Pair Share on Social Attitudes of Elementary School Students - Cindy Indah Sari; Chumi Zahroul Fitriyah; Dyah Ayu Puspitaningrum (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2025)
This study examines the effect of the Think Pair Share (TPS) cooperative learning model on students' social attitude scores in fourth-grade students at SDN Patrang 1 Jember. Social attitudes, including cooperation, respect, and responsibility, are essential aspects of character education that can be fostered through interactive learning approaches. This research employs a quasi-experimental method with a Nonequivalent Control Group design, comparing two groups: an experimental class implementing TPS and a control class using the Inquiry Learning model. The sample consists of two fourth-grade classes selected purposively. Data were collected through observation and assessment of students' social attitudes and analyzed using an independent sample t-test with SPSS version 26. The findings reveal a significant difference of 19.1% between the experimental and control classes, with the TPS class demonstrating higher social attitude scores. The statistical test results indicate that tcalculated (14.759) exceeds ttable (2.008), confirming the significant effect of TPS on social attitudes. The study concludes that the TPS model effectively enhances students' social attitudes by encouraging structured peer interaction and discussion. These results highlight the potential of cooperative learning strategies in improving character education, particularly in fostering positive social behaviors among elementary school students.